2016
DOI: 10.1128/jvi.00242-16
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Integration over Time Supports a Role for Cytotoxic T Lymphocytes and Ongoing Replication as Determinants of Reservoir Size

Abstract: The dynamics of HIV reservoir accumulation off antiretroviral therapy (ART) is underexplored. Levels of integrated HIV DNA in peripheral blood mononuclear cells (PBMCs) were longitudinally monitored before and after antiviral therapy. HIV integration increased over time in both elite controllers (ECs; n ‫؍‬ 8) and noncontrollers (NCs; n ‫؍‬ 6) before ART, whereas integration remained stable in patients on ART (n ‫؍‬ 4). The median annual fold change was higher in NCs than in ECs and negatively correlated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
17
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 54 publications
4
17
1
Order By: Relevance
“…Moreover, Buzon et al [ 57 ] found treating the earliest stages Fiebig III/IV resulted in a larger drop in integrated HIV DNA than treating in Fiebig V; uniquely, the decline in integrated HIV continued in those patients treated at the very earliest stages over several years. Pre-ART integration levels also correlated with viral load (r = 0.86) and negatively correlated with CD4/CD8 ratio (r = − 0.52), consistent with the idea that integrated HIV DNA can provide a surrogate marker for reservoir size [ 54 ] and consistent with [ 34 , 56 , 58 ]. These longitudinal studies highlight that integrated HIV DNA measures provide different and complementary information to total HIV DNA when an excess of unintegrated HIV DNA may exist.…”
Section: The Challenge Of Measuring Hiv Reservoir Sizesupporting
confidence: 77%
See 3 more Smart Citations
“…Moreover, Buzon et al [ 57 ] found treating the earliest stages Fiebig III/IV resulted in a larger drop in integrated HIV DNA than treating in Fiebig V; uniquely, the decline in integrated HIV continued in those patients treated at the very earliest stages over several years. Pre-ART integration levels also correlated with viral load (r = 0.86) and negatively correlated with CD4/CD8 ratio (r = − 0.52), consistent with the idea that integrated HIV DNA can provide a surrogate marker for reservoir size [ 54 ] and consistent with [ 34 , 56 , 58 ]. These longitudinal studies highlight that integrated HIV DNA measures provide different and complementary information to total HIV DNA when an excess of unintegrated HIV DNA may exist.…”
Section: The Challenge Of Measuring Hiv Reservoir Sizesupporting
confidence: 77%
“…Meanwhile the rate of decay for total HIV was similar for both groups. Pinzone et al showed that acutely infected individuals exhibited a significant drop in integrated HIV levels 12 months after ART initiation, while integration levels barely changed in patients treated during chronic infection [ 54 ], consistent with Koelsch et al [ 55 ]. Moreover, Buzon et al [ 57 ] found treating the earliest stages Fiebig III/IV resulted in a larger drop in integrated HIV DNA than treating in Fiebig V; uniquely, the decline in integrated HIV continued in those patients treated at the very earliest stages over several years.…”
Section: The Challenge Of Measuring Hiv Reservoir Sizesupporting
confidence: 71%
See 2 more Smart Citations
“…Prior to treatment initiation, total and integrated HIV DNA levels are higher in individuals treated during chronic HIV infection and decrease to a lower extent than those treated in primary HIV infection [ 71 73 ]. Furthermore, integrated HIV DNA continues to decay after prolonged therapy in individuals treated during primary infection suggesting that enhanced immune responses in these individuals are able to clear HIV infected cells more effectively [ 72 , 74 , 75 ]. During this same period, CD4 cell numbers typically increase with a measure of immune restoration.…”
Section: Dynamics Of Hiv Infected Populationsmentioning
confidence: 99%